preplogic

Notes for the course "elementary logic"
git clone https://git.tronto.net/preplogic
Download | Log | Files | Refs | README

preplogic-solutions.tex (10143B)


      1 \documentclass[a4paper,oneside]{article}
      2 \usepackage[utf8]{inputenc}
      3 \usepackage{amsmath}
      4 \usepackage{amsthm}
      5 \usepackage{amssymb}
      6 \usepackage[top=2cm]{geometry}
      7 
      8 \theoremstyle{definition} \newtheorem{exercise}{Exercise}[section]
      9 
     10 \author{Sebastiano Tronto (\texttt{sebastiano.tronto@uni.lu})}
     11 \title{Elementary Logic exercises (Prep Camp 2020)}
     12 
     13 \begin{document}
     14 \maketitle
     15 
     16 \section{Logical operations}
     17 
     18 \begin{exercise}
     19   Determine if the following statements are \textbf{true} or \textbf{false}:
     20   \begin{enumerate}
     21     \item ``Today is Tuesday or Germany has more inhabitants than Luxembourg''
     22     \item ``$7$ is odd and $2+2=5$''
     23     \item Every number of the form $2^{2^n}+1$, for $n=1,2,3...$, is prime.
     24   \end{enumerate}
     25 \end{exercise}
     26 \begin{proof}[Solution]
     27   \begin{enumerate}
     28     \item \textbf{True}: regardless of when you solve this exercise, Germany
     29           has more inhabitants than Luxembourg.
     30     \item \textbf{True}
     31     \item \textbf{False}: the number $2^{2^5}+1=4294967297=641\times 6700417$
     32           is not prime.
     33   \end{enumerate}
     34 \end{proof}
     35 
     36 \begin{exercise}
     37   What is the negation of the sentence ``\emph{I payed attention in class and I
     38   did not do my homework}'' ?
     39 \end{exercise}
     40 \begin{proof}[Solution]
     41   ``\emph{I did not pay attention in class \textbf{or} I did my homework}''
     42 \end{proof}
     43 
     44 \begin{exercise}
     45   Simplify the following logical expressions using the properties of logical
     46   operations (where $A,B$ and $C$ are statements):
     47   \begin{enumerate}
     48     \item $A\land(A\lor B)$
     49     \item $A\lor (B\land A)$
     50     \item $(A\lor B) \land \neg A$
     51     \item $A \lor (\neg A\land B)$
     52     \item $(\neg (A\lor \neg B))\land ((A\lor C) \land \neg C)$
     53   \end{enumerate}
     54 \end{exercise}
     55 \begin{proof}[Solution]
     56   They are equivalent to the following (you can check with truth tables):
     57   \begin{enumerate}
     58     \item $A$
     59     \item $A$
     60     \item $B\land \neg A$
     61     \item $A\lor B$
     62     \item Let's do this one in more steps:
     63       \begin{align*}
     64         (\neg (A\lor \neg B))\land ((A\lor C) \land \neg C)=
     65         &(\neg A\land B)\land ((A\lor C)\land \neg C)=\\
     66         =&(\neg A\land B)\land ((A\land \neg C)\lor (C\land \neg C))=\\
     67         =&(\neg A\land B)\land ((A\land \neg C)\lor \textbf{false})=\\
     68         =&(\neg A\land B)\land (A\land \neg C)=\\
     69         =&A\land \neg A\land B\land \neg C=\\
     70         =&\textbf{false}
     71       \end{align*}
     72   \end{enumerate}
     73 \end{proof}
     74 
     75 \section{Implication}
     76 
     77 \begin{exercise}
     78   Fill in the following truth table:
     79   \begin{align*}
     80     \begin{array}{|c|c|c|c|c|}
     81       \hline
     82       A & B & C & \neg(A\implies B) & (A\implies B) \implies C \\
     83       \hline
     84       0 & 0 & 0 & 0 & 0 \\
     85       \hline
     86       0 & 0 & 1 & 0 & 1 \\
     87       \hline
     88       0 & 1 & 0 & 0 & 0 \\
     89       \hline
     90       0 & 1 & 1 & 0 & 1 \\
     91       \hline
     92       1 & 0 & 0 & 1 & 1 \\
     93       \hline
     94       1 & 0 & 1 & 1 & 1 \\
     95       \hline
     96       1 & 1 & 0 & 0 & 0 \\
     97       \hline
     98       1 & 1 & 1 & 0 & 1 \\
     99       \hline
    100     \end{array}
    101   \end{align*}
    102 \end{exercise}
    103 
    104 \begin{exercise}[Transitivity]
    105   Prove that the following statement is true for any statements $A,B$ and $C$:
    106   \begin{align*}
    107     ((A\implies B)\land (B\implies C))\implies (A\implies C)
    108   \end{align*}
    109 \end{exercise}
    110 \begin{proof}[Solution]
    111   Let's rewrite the first part in terms of basic logical operations:
    112   \begin{align*}
    113     (A\implies B)\land (B\implies C)=&(B\lor \neg A)\land(C\lor \neg B)
    114   \end{align*}
    115   now we can write a truth table for the two parts
    116   \begin{align*}
    117     \begin{array}{|c|c|c|c|c|}
    118       \hline
    119       A & B & C & (B\lor\neg A)\land(C\lor\neg B) & A\implies C \\
    120       \hline
    121       0 & 0 & 0 & 1 & 1 \\
    122       \hline
    123       0 & 0 & 1 & 1 & 1 \\
    124       \hline
    125       0 & 1 & 0 & 0 & 1 \\
    126       \hline
    127       0 & 1 & 1 & 1 & 1 \\
    128       \hline
    129       1 & 0 & 0 & 0 & 0 \\
    130       \hline
    131       1 & 0 & 1 & 0 & 1 \\
    132       \hline
    133       1 & 1 & 0 & 0 & 0 \\
    134       \hline
    135       1 & 1 & 1 & 1 & 1 \\
    136       \hline
    137     \end{array}
    138   \end{align*}
    139   With the help of the truth table we see that whenever the first part
    140   ``$(\neg (A\lor \neg B))\land ((A\lor C) \land \neg C)$'' is true, also the
    141   implication ``$A\implies C$'' is true. This shows that the ``big
    142   implication'' is true. (If you are not convinced, you can add more details to
    143   this proof, for example by writing more truth tables.)
    144 \end{proof}
    145 
    146 \begin{exercise}
    147 What is the contrapositive of ``\emph{If this table is not reserved, we sit
    148 here}'' ?
    149 \end{exercise}
    150 \begin{proof}[Solution]
    151   ``\emph{If we do not sit here, this table is reserved}''. One could also say
    152   this in another way, for example ``\emph{We do not sit here because this
    153   table is reserved}''.
    154 \end{proof}
    155 
    156 \section{Quantifiers}
    157 
    158 \begin{exercise}
    159   Write the negation of the following statements:
    160   \begin{enumerate}
    161     \item $\exists x\in \mathbb N,\, x^2-2=0$
    162     \item ``Every prime number is odd''
    163     \item ``Every person I have met likes pizza''
    164     \item ``There is at least one number greater than $7$''
    165     \item $\forall x\in \mathbb N,\,x\geq 0$
    166     \item $\forall x\in \mathbb Z,\,(\exists y\in\mathbb Z,\,x+y=0)$
    167   \end{enumerate}
    168 \end{exercise}
    169 \begin{proof}[Solution]
    170   \begin{enumerate}
    171     \item $\forall x\in\mathbb N,\, x^2-2\neq 0$
    172     \item ``There is at least one prime number which is even''
    173     \item ``I have met at least one person that does not like pizza''
    174     \item ``Every number is less or equal than $7$''
    175     \item $\exists x\in\mathbb N,\, x<0$
    176     \item $\exists x\in \mathbb Z,\, (\forall y\in \mathbb Z,\, x+y\neq 0)$
    177   \end{enumerate}
    178 \end{proof}
    179 
    180 \begin{exercise}
    181   There is another quantifier that we did not cover in the lecture, namely
    182   $\exists!$ (read ``there exists exactly one''). For example, the sentence
    183   ``\emph{there exists exactly one natural number x such that x+2=5}'' can be
    184   written in symbols as ``$\exists!x\in \mathbb N,\,x+2=5$''.
    185 
    186   In this exercise, your task is to give a formal definition of this quantifier
    187   using the logical symbols that we have defined in class. In particular, you
    188   will need the following:
    189   \begin{itemize}
    190     \item the universal ($\forall$) and existential ($\exists$) quantifiers
    191     \item the conjunction $\land$
    192     \item the implication $\implies$
    193   \end{itemize}
    194   Moreover, you will need the equality symbol $=$ between two elements of a set
    195   (if $a$ and $b$ are two elements of the same set, ``$a=b$'' is a mathematical
    196   statement and it is \textbf{true} if and only if $a$ and $b$ are the same
    197   element).
    198   
    199   \emph{Warning: your definition must depend on a set $S$ and on a ``variable
    200   statement'' $A(x)$, as the existential and universal quantifiers.}
    201 \end{exercise}
    202 \begin{proof}[Solution]
    203   The idea is that we want to write ``\emph{there is $x\in S$ such that $A(x)$
    204   is true, \textbf{and}, for any other $y\in S$, $A(y)$ is false}. From this 
    205   we see that the structure of the statement is
    206   \begin{align*}
    207     \exists x\in S,\,(\text{``something''}\land\text{``something else''})
    208   \end{align*}
    209   The ``something'' part is just $A(x)$. The ``something else'' part can be
    210   written in different ways, for example
    211   \begin{align*}
    212     \forall y\in S,\,(y\neq x\implies \neg A(y)) \quad \text{or}
    213     \quad \forall y\in S,\,(A(y)\implies y=x)
    214   \end{align*}
    215   (notice that the two implications above are one the contrapositive of the
    216   other); or also
    217   \begin{align*}
    218     \forall y\in S\setminus \{x\},\, \neg A(y)
    219   \end{align*}
    220   So in conclusion, one way to define ``$\exists!$'' is the following:
    221   \begin{align*}
    222     \exists!x\in S,\,A(x)\quad:=\quad\exists x\in S,\,(A(x)\land
    223     (\forall y\in S,\,(A(y)\implies y=x)))
    224   \end{align*}
    225     
    226 \end{proof}
    227 
    228 \section{Proofs}
    229 
    230 \begin{exercise}
    231   Prove by induction that
    232   \begin{align*}
    233     \forall n\in\mathbb N,\quad \sum_{k=1}^n(2k-1)=n^2
    234   \end{align*}
    235     (here $\sum_{k=1}^n(2k-1)$ means $1+3+5+\cdots+ (2n-1)$).
    236 \end{exercise}
    237 \begin{proof}[Solution]
    238   \textbf{Base case:} for $n=0$ the sum is empty, so we have $0=0$ which is
    239   true. (If you do not think that the formula makes sense for $n=0$, you can do
    240   prove it for $n\geq 1$ and fo $n=1$ as a base case.)
    241 
    242   \textbf{Inductive step:} we can assume that the formula works for a generic
    243   (but fixed) $n\in\mathbb N$ and prove that then it also works for $n+1$. So:
    244   \begin{align*}
    245     \sum_{k=1}^{n+1}(2k-1)&=\left(\sum_{k=1}^{n}(2k-1)\right)+2(n+1)-1=\\
    246                           &=n^2 +2(n+1)-1=\\
    247                           &=n^2+2n+1=\\
    248                           &=(n+1)^2
    249   \end{align*}
    250   which is the formula for $n+1$.
    251 \end{proof}
    252 
    253 \begin{exercise}
    254   If $n\in \mathbb N$ the \emph{factorial} of $n$, denoted by $n!$ is defined
    255   as follows:
    256   \begin{align*}
    257     n!=\begin{cases}
    258       1&\text{if } n=0,\\
    259       n\times (n-1)! & \text{if } n> 0.
    260     \end{cases}
    261   \end{align*}
    262   Prove by induction that if $n\geq 4$ then $n!\geq 2^n$.
    263 \end{exercise}
    264 \begin{proof}[Solution]
    265   \textbf{Base case:} here the base case is $n=4$, and we have
    266   $4!=24\geq 16=2^4$.
    267 
    268   \textbf{Inductive step:} we can assume that the inequality is true for $n$,
    269   and prove that it is also true for $n+1$. We have:
    270   \begin{align*}
    271     (n+1)!=(n+1)\times n!\geq (n+1)\times 2^n\geq 2^{n+1}
    272   \end{align*}
    273 \end{proof}
    274 
    275 \begin{exercise}
    276   Is the following statement true or false? Give a proof of your answer.
    277   \begin{align*}
    278     \forall n\in \mathbb N,\, n^2 -4n +5>n
    279   \end{align*}
    280 \end{exercise}
    281 \begin{proof}[Solution]
    282   The statement is \textbf{false}. Since it starts with a universal
    283   quantifier, in order to prove that it is false we just need to provide one
    284   example of $n\in \mathbb N$ which makes it false. In other words, we need to
    285   prove that
    286   \begin{align*}
    287     \exists n\in \mathbb N,\, n^2-4n+5\leq n
    288   \end{align*}
    289   and a proof of this fact is very simple: for $n=2$ we have
    290   $2^2-4\times 2+5=1\leq 2$.
    291 \end{proof}
    292 
    293 \begin{exercise}
    294   Do the last point of Exercise 1.1 again, but this time give a proof of your
    295   answer.
    296 \end{exercise}
    297 \begin{proof}[Solution]
    298   Again, since we have to prove that the statement is false, we just need to
    299   show one counterexample. for example, the number
    300   $2^{2^5}+1=4294967297=641\times 6700417$ is not prime.
    301 \end{proof}
    302 
    303 
    304 
    305 
    306 \end{document}